2008
DOI: 10.1021/ja804398y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Combinatorial Selection of Molecules Capable of Inhibiting the (CUG) Repeat RNA−MBNL1 Interaction In Vitro: Discovery of Lead Compounds Targeting Myotonic Dystrophy (DM1)

Abstract: Myotonic dystrophy type 1 (DM1), the most common form of muscular dystrophy in adults, is an RNA-mediated disease. Dramatically expanded (CUG) repeats accumulate in nuclei, and sequester RNA-binding proteins such as the splicing regulator MBNL1. We have employed resin-bound dynamic combinatorial chemistry (RBDCC) to identify the first examples of compounds able to inhibit MBNL1 binding to (CUG) repeat RNA. Screening an RBDCL with a theoretical diversity of 11,325 members yielded several molecules with signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
163
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(164 citation statements)
references
References 49 publications
0
163
0
Order By: Relevance
“…8). [10,35,42] The 22 nucleotide hairpin sequence in the HIV-1 frameshift stem-loop RNA was targeted . Structures of (a) oxazole-based peptide macrocycle 7, (b) cationic benzylic thiols, and (c) neutral carboydrate benzylic thiols used to generate a dynamic combinatorial library for recognition of quadruplex DNA targets.…”
Section: Rnamentioning
confidence: 99%
See 2 more Smart Citations
“…8). [10,35,42] The 22 nucleotide hairpin sequence in the HIV-1 frameshift stem-loop RNA was targeted . Structures of (a) oxazole-based peptide macrocycle 7, (b) cationic benzylic thiols, and (c) neutral carboydrate benzylic thiols used to generate a dynamic combinatorial library for recognition of quadruplex DNA targets.…”
Section: Rnamentioning
confidence: 99%
“…In an independent study, the same library was screened for target compounds able to inhibit muscular dystrophy type 1 (MBNL1) binding to (CUG) repeat RNA. [42] Four lead compounds were identified and inhibited the interaction of GGG(CUG) 109 GGG RNA with MBNL1 in vitro with K i values in the low micromolar range. In a very recent study, the olefin and hydrocarbon isosteres of 14, compounds 15 and 16 respectively (Fig.…”
Section: Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that expanded CTG-induced effects could be reverted if CTG-repeat transgene expression was interrupted in a DM1 mouse model. Several other groups developed synthetic molecules and (CAG)n oligonucleotides that disrupted MBNL1 interaction with expanded CUG repeats (17)(18)(19)(20)(21)(22). However, those approaches may not address all the pathological consequences of expanded CUG RNAs.…”
mentioning
confidence: 99%
“…Diseases in which RNA repeats are found within a specific gene include spinocerebellar ataxia type 3 (sCA3) and Huntington's disease (HD). 3 "In theory, inhibiting the interaction of proteins with toxic RNA could be useful for any RNA-dominant disease caused by expanded repeats," Thornton told SciBX. "Other diseases caused by expanded repeats within untranslated regions are rare, but myotonic dystrophy type 2 (DM2) might be a logical disease to target, " he added.…”
mentioning
confidence: 99%